The socio-institutional dimension of the problem of scholasticism in the Argentine Psychology - Lucas David Tosi; Jeremías David Tosi (Interacciones)
Background: Scholasticism in the Psychology of Argentina is a problem that has not yet been overcome. In this country, different kinds of fragmentation of the discipline (e.g., between cultural and biological approaches) and hegemony of psychoanalysis are still in force. This problem has been analyzed in both individual and socio-institutional level. At individual level, two types of attitudes have been differentiated: dogmatic - represented by those who seek to preserve the scholastic condition-, and scientific -represented by those who seek to overcome this situation-. While the dogmatic attitudes are part of the problem, focusing on them could have undesirable consequences. Method: This study warns about the risks of analyzing the scholasticism in terms of "dogmatic individual". The present is a theoretical study. Conclusion: The psychologization of scholasticism and the invisibility of supra-individual factors (i.e. socio-institutional) are some of its consequences. The problem of the argentine scholasticism depends, in part, on socio-institutional factors. In practical terms, places of dialogue to analyze critically the different levels of the problem (individual and socio-institutional) should be developed.